Informational Vulnerability of Russian University Students to Adverse Impact of Social Media - V. M. Kiselev (Вестник Российского экономического университета имени Г. В. Плеханова)
Concern for the health of young citizens is a major task of our state, it was included in the target program ‘Research and Development on Priority Lines of Developing Scientific and Technological Complex in Russia for 2014-2021’. This concern can be realized relying on effective technologies of influencing media, popularization of healthy life style, etc. However, not a single social and psychological theory can cover the whole diversity of social world, but each of them can more or less adequately explain separate, local aspects, phenomena, facts and regularities. The goal of the article is to verify the hypothesis about possible foresight of events and their drastic consequences, including youth extremism, which can take place in case of young students’ exposure to adverse impact on the part of media and about expediency to protect students at every university from this factor. Nature of this phenomenon and consequences of its proliferation have been analyzed in various academic works. Multi-disciplinary methods can be useful for studying the problem. Sociological methods collect and process information mainly in the form of survey and document analysis (event registration, information gained from respondents). The use of neuro-physiological methods stipulates device registration of neuro-physiological processes in the cerebral cortex and adjoining sub cortex zone, which cause psychic functions of the human being uncontrolled by him/her. Philosophy uses logical methods to find reasons of phenomena and their consequences. The combined use of these inter-disciplinary theories and research methods can help reveal sociological and philosophic aspects of social media, understand nature of their impact on student behavior. By social media calls for extremism and terrorism are spread among students and in conditions of present information war waged by western special services against the Russian Federation it is extremely risky and requires a quick response. Findings of the research can help find effective sociological counteraction against youth extremism and terrorism.